Texture of onions before and after freeze-drying. - Guiné, Raquel (2010)
Dehydrated onion is widely used as flavor additive in the manufacture of processed foods and many other convenience foods. However, when drying shelf-stable vegetables it is absolutely essential to preserve their desired quality attributes. In the present work fresh and freeze-dried onions were analysed in terms of Texture Profile Analysis (TPA) to evaluate in what extent this operation influences the texture attributes of onions. From the analysis made to the onions, it was observed that the fresh onion had 90.02 ( ± 1.20) % moisture (wet basis) and the freeze-drying operation reduced the moisture content to 5.19 ( ± 0.38) % (w.b.). The results shows that the hardness of the fresh onion is very much higher than that of the freeze- dried, being the average value for hardness of the fresh onion 12.87 ( ± 2.24) N and that for the freeze- dried 3.50 ( ± 0.70) N. The cohesiveness increases slightly with drying, from an average of 0.41 ( ± 0.03) in the fresh form to 0.65 ( ± 0.07) in the freeze-dried product. The values for springiness, 78.72 ( ± 13.78) % for the fresh and 74.64 ( ± 4.51) % for the dried onion, are very similar, indicating that this drying treatment did not affect this property. In the fresh state, the onions show an average chewiness of 4.03 ( ± 0.49) N and after the freeze-drying treatment the chewiness diminished to 1.68 ( ± 0.32) N.